Association between obstructive sleep apnea and male reproductive function: a cross-sectional study with stratified analysis - Zhang, Wei; Wu, Xu; Zhang, Yuyang; Gao, Hui; Liu, Guodong; Geng, Hao; Zou, Ci; Zhang, Xiansheng (Frontiers in Endocrinology, 2025)
ObjectiveObstructive sleep apnea hypopnea syndrome (OSAHS) is a common sleep disorder known to affect systemic physiology. Emerging evidence suggests a potential relationship between OSA and male reproductive health, but this association remains insufficiently characterized. This study aims to explore the link between OSA, semen quality, and sex hormone profiles in reproductive-aged men.MethodA total of 108 newly diagnosed OSA patients aged 20–40 years, who underwent full-night polysomnography (PSG) at the Respiratory Sleep Center of the Second Affiliated Hospital of Anhui Medical University between 2022 and 2024, were included. The control group consisted of 84 healthy adult males undergoing fertility evaluations during the same period at the same hospital. All participants completed physical examinations, semen analysis, and sex hormone testing. OSA severity was classified based on the apnea–hypopnea index (AHI) obtained from PSG in the patient group.ResultsCompared with controls, men with OSA had significantly higher body weight and BMI, as well as lower sperm concentration (90.0 vs. 129.3 ×106ml), total motility (68.6% vs. 71.0%), progressive motility (63.8% vs. 66.6%), and testosterone levels (13.1 vs. 21.8 nmol/L) (all p < 0.01). Stratified analyses showed a stepwise decline in semen parameters and oxygen saturation with increasing OSA severity. In multivariable analysis, AHI was independently associated with reduced sperm concentration (β = –0.393), total motility (β = –0.640), and progressive motility (β = –0.623) (all p < 0.001).ConclusionOSA is independently associated with impaired semen quality and lower testosterone levels in reproductive-aged men. These findings highlight the potential reproductive consequences of untreated OSA and underscore the importance of early screening and intervention.